Penerapan Digital Marketing Sebagai Media Penjualan Agribisnis Dengan Teknik Hidroponik Desa Karang Rahayu Kab Bekasi - Fitri Rezeki; Yuan Badrianto (Joong-Ki : Jurnal Pengabdian Masyarakat, 2022)
Digital marketing is very helpful for business people in interacting with consumers directly to producers, to meet the company's operational needs, the ease obtained from digital marketing is expected to develop the agribusiness industry located in Karang Rahayu Village of South Cikarang District of Bekasi Regency. Limited land in the middle of the city becomes a obstaclesto develop hydroponic cultivation. The lack of understanding of the people of Karang Rahayu Village regarding the opportunities of the agribusiness industry and hydroponic cultivation is the main problem that must be resolved immediately. The lack of ability to market will also have an impact on business prospects so that it is necessary to conduct Training on the Application of Digital Marketing as a Medium of Agribusiness Sales with Hydroponic Techniques in Karang Rahayu Village, Bekasi Regency. In community service in Karang Rahayu Village, South Cikarang Subdistrict, there are 4 methods used including observation methods, interview methods and training methods. The results achieved by Training in The Implementation of Digital Marketing as a Medium of Agribusiness Sales with Hydroponic Techniques in Karang Rahayu Village of Bekasi Regency from PKK Mothers earn additional income thanks to hydroponic cultivation and reach broad segmentation to exit the island by utilizing digital marketing.